2017
DOI: 10.20448/2002.11.34.45
|View full text |Cite
|
Sign up to set email alerts
|

Interest Rate Spread on Bank Profitability: The Case of Ghanaian Banks

Abstract: The banking sector in Ghana plays a dominant role in the financial sector, particularly with respect to mobilization of savings and the provision of credit. An analysis of bank interest rate spreads is therefore central to the understanding of the financial intermediation process and the macroeconomic environment in which banks operate. This paper is motivated by the fact that although Ghana's financial sector was liberalized in the early 1990s to allow for market determination of interest rates, concerns abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
(22 reference statements)
2
4
0
Order By: Relevance
“…Because, risk averse bank tend to be reluctant to engage in riskier lending activities and larger bank tend to be more confident to charge higher loan rate and low deposit rate. This result also in line with previous research by (Antwi et al, 2017) towards banking sector in Ghana, the bigger the bank size, higher interest spread.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Because, risk averse bank tend to be reluctant to engage in riskier lending activities and larger bank tend to be more confident to charge higher loan rate and low deposit rate. This result also in line with previous research by (Antwi et al, 2017) towards banking sector in Ghana, the bigger the bank size, higher interest spread.…”
Section: Discussionsupporting
confidence: 92%
“…Higher inflation will lead to uncertainty condition and induce the need of banks to raise interest rate spread in order to compensate this condition. This result supported by previous research by (Antwi et al, 2017). Bank's Net Interest Margin: Study Case in Indonesia, Thailand, and Philippines. Vina Nugroho, Kim Sung Suk…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Peshev's (2015) conclusion in the case of commercial banks in Bulgaria was that the positive relationship was as a result of banks raising their lending rates and lowering deposit rates to raise profitability. In their study on interest rate spread and profitability in Ghanaian banks, Antwi et al (2017) found return on assets to have a significant positive effect on interest rate spread pointing to a profit maximizing behaviour among the banks. Banks with higher profits relative to average assets tended to have higher lending rates and lower deposit rates.…”
Section: Discussion Of Findingsmentioning
confidence: 97%
“…Another study found five similar characteristics: (1) being creative (2) continuously looking to make a difference, (3) participating in a global vision to drive change and collaboration, (4) remaining inquisitive to learn and adapt to change, and (5) acquiring in-depth knowledge and competence (Zhu, 2015). Yet another study also found leaders are required to be not only creative and innovative but also able to collaborate to seize opportunities (Sandell, 2013;Owusu-Antwi, Banerjee, & Antwi, 2017;Ahmed, Rehan, Chhapra, & Supro, 2018). Hence, in this study, we used the following dimensions of digital leadership: creativity, in-depth knowledge, global vision and collaboration, reflectiveness, and inquisitiveness.…”
Section: Introductionmentioning
confidence: 99%